Multi-layer cementitious composition prefabricated uniform-section structural material
By spraying and curing the expansion first cementitious material on the inner surface of the outer layer of the pipeline, a mechanically coupled composite structure between the inner layer and the outer layer is formed, the fault problem of the pipeline under mechanical load and environmental stress is solved, and the effect of high load bearing and reducing fault events is achieved.
Patent Information
- Application Number
- CN202380053698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-10
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-07
AI Technical Summary
Existing pipelines are prone to rupture, peeling and debris accumulation when facing mechanical loads and environmental stresses, resulting in cost, environmental damage and safety issues.
Using a composite structure including an inner layer and an outer layer of an expansive first cementitious material, a composite structure with mechanical coupling is formed by spraying and curing the uncured first cementitious material on the inner surface of the outer layer.
The composite material is able to withstand high internal and external loads, reduce failure events, provide improved structural load bearing capacity, and reduce space between the inner and outer layers through the use of expandable materials, thereby increasing adhesion.
Smart Images

Figure CN119585228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a multilayer composite structure comprising a cementitious layer which expands when cured. The present invention also relates to the preparation of the composite structure and the use of the composite structure, for example as a pipeline or a building component. Background Art
[0002] Pipelines are important infrastructure and are used to transport and distribute commodities such as oil, gas and water. Pipelines used to achieve these purposes are often subject to heavy mechanical loads and environmental stresses. As a result, metal pipes and concrete pipes are susceptible to problems such as cracking, spalling and debris accumulation. Metal pipes can corrode or deform.
[0003] In various applications where pipeline infrastructure is used, failure of pipelines can create significant costs, environmental damage, and / or safety issues. Leakage of drinking water is a well-known problem, with major cities such as Boston losing approximately 70 million gallons of drinking water per day since the late 1970s. Leakage from underground sewage lines can cause contamination of aquifers. Leakage from gas lines is known to cause large-scale fires.
[0004] One option for addressing failures in pipeline infrastructure is to repair or recondition an existing pipeline by means of a sprayable cementitious material. WO 2021 / 167635 A1 discloses a method for repairing or reconditioning an existing pipeline by means of a fiber reinforced engineered cementitious composite (ECC). The method described in WO 2021 / 167635 A1 is for providing a repaired or reconditioned pipeline having, for example, a higher load and bending capacity than the original pipeline and thus reducing the number of failure events in the pipeline.
[0005] However, in certain circumstances it would be advantageous to provide a prefabricated pipeline having improved properties for withstanding higher internal and / or external loads than conventional pipelines.
[0006] It is an object of the present invention to go some way to satisfying this list of needs; and / or at least to provide the public with a useful choice.
[0007] Other objects of the present invention will become apparent from the following description which is given by way of example only.
[0008] Any description of documents, acts, materials, devices or objects etc. included in this specification is only for the purpose of providing a context for the present invention. It should not be taken as an admission that any or all of these matters form part of the prior art base or are common general knowledge in the field relevant to the present invention because they existed before the priority date. Summary of the invention
[0009] In a first aspect, the present invention provides a composite member comprising:
[0010] an inner layer comprising a first cement material, and
[0011] An outer layer, wherein the inner layer substantially covers an inner surface of the outer layer and the first cement material is an intumescent material that applies a force to the inner surface of the outer layer.
[0012] In a second aspect, the present invention provides a method of manufacturing a composite member according to the first aspect, the method comprising:
[0013] spraying an uncured mixture of the first cement material onto the inner surface of the outer layer; and
[0014] The first cementitious material is cured to obtain the composite structure.
[0015] In a third aspect, the present invention provides a method of manufacturing a composite member comprising an inner layer, a formwork layer and an outer layer, the inner layer comprising a first cementitious material that expands when cured, wherein the inner layer contacts an outer surface of the formwork layer and an inner surface of the outer layer, wherein the method comprises:
[0016] providing the template layer and the outer layer with a cavity between the two layers;
[0017] casting an uncured mixture of the first cementitious material into the cavity between the formwork layer and the outer layer; and
[0018] The first cementitious material is cured to provide the composite member.
[0019] In a fourth aspect, the present invention provides a composite member prepared according to the second or third aspect.
[0020] In certain embodiments, the first cementitious material has a maximum expansion of at least about 1200 με. In certain other embodiments, the first cementitious material has a maximum expansion of at least about 3000 με, about 3375 με, about 4000 με, or about 4450 με.
[0021] In certain embodiments, the outer layer comprises a second cementitious material. In certain embodiments, the second cementitious material shrinks when cured. In certain embodiments, the second cementitious material has a shrinkage of less than about 500 μm when cured. In certain embodiments, the second cementitious material has a shrinkage of about 50 to about 500 μm when cured. In certain embodiments, the second cementitious material has a shrinkage of about 100 to about 400 μm when cured. In certain embodiments, the second cementitious material has a shrinkage of about 50 μm, about 100 μm, about 150 μm, about 200 μm, about 250 μm, about 300 μm, about 350 μm or about 400 μm when cured.
[0022] In certain embodiments, the second cementitious material has a contraction of less than about 1000 με when cured. In certain embodiments, the second cementitious material has a contraction of less than about 500 με when cured. In certain embodiments, the second cementitious material has a contraction of about 50 to about 500 με when cured. In certain embodiments, the second cementitious material has a contraction of about 100 to about 400 με when cured. In certain embodiments, the second cementitious material has a contraction of about 50 μm, about 100 με, about 150 με, about 200 με, about 250 με, about 300 με, about 350 με, or about 400 με when cured. In certain embodiments, the second cementitious material has a contraction of about 300 to about 350 με when cured.
[0023] In some embodiments, the first cementitious material and / or the second cementitious material comprises a composite binder. In some embodiments, the composite binder comprises a cement component and a cement component. In some embodiments, the cement component comprises hydraulic cement.
[0024] In certain embodiments, the first cement material and / or the second cement material comprises fibers.
[0025] In certain embodiments, the first cementitious material and / or the second cementitious material comprises a fiber reinforced engineered cementitious composite.
[0026] In certain embodiments, the first cement material and / or the second cement material is sprayable.
[0027] In certain embodiments, the cement component of the first cementitious material comprises an expansive agent. In certain embodiments, the expansive agent is calcium sulfoaluminate.
[0028] In some embodiments, the inner layer covers substantially all of the inner surface of the outer layer. In some embodiments, the outer layer covers substantially all of the outer surface of the inner layer.
[0029] In some embodiments, the outer layer comprises a metal, a polymer, a composite, or a combination of any two or more thereof. In some embodiments, the metal is steel. In some embodiments, the polymer is polyvinyl chloride (PVC). In some embodiments, the composite is a fiber reinforced plastic.
[0030] In certain embodiments, the template layer comprises a metal, a polymer, a composite, or a combination of any two or more thereof.
[0031] In certain embodiments, the composite member is prefabricated.
[0032] In some embodiments, the composite member is hollow. In some embodiments, the composite member is solid. In some embodiments, the composite member is in the shape of a tube, a column or a plate. In some embodiments, the cross-section of the composite member is circular, oval, square, rectangular, pentagonal, hexagonal, heptagonal or octagonal.
[0033] In another aspect, the present invention provides use of the composite member of the first or fourth aspect as a tube, wherein the composite member is hollow.
[0034] In certain embodiments, the cross-section of the composite member is circular.
[0035] In certain embodiments, the tube is used to transport water, gas, or oil.
[0036] In yet another aspect, the present invention provides use of the composite member of the first or fourth aspect as a building component.
[0037] In certain embodiments, the building component is a column or a panel.
[0038] The present invention may also be broadly described as consisting of the parts, components and features mentioned or described in the specification of this application, individually or collectively, and any or all combinations of any two or more of the parts, components and features, and where the specific entities described herein have known equivalents in the art related to the present invention, the known equivalents are deemed to be incorporated herein as if individually set forth.
[0039] In addition, where features and aspects of the invention are described in terms of Markush groups, one skilled in the art will recognize that the invention is also thereby described in terms of any individual member or subgroup of members of the Markush group.
[0040] As used herein, the "plural form" of a noun refers to the plural and / or singular form of the noun.
[0041] The term "and / or" as used herein means "and" or "or" or both.
[0042] The term "comprising" as used in this specification means "consisting at least in part of..." When each statement including the term "comprising" is described in this specification, it may also have features other than those prefaced by the term. Related terms such as "comprising" and "including" may be interpreted in the same way.
[0043] It is intended that reference to a numerical range disclosed herein (e.g., 1 to 10) also incorporates reference to all rational numbers within that range (e.g., 1, 1.1, 2, 3, 3.9, 4, 5, 6, 6.5, 7, 8, 9, and 10) and any range of rational numbers within that range (e.g., 2 to 8, 1.5 to 5.5, and 3.1 to 4.7) and that all subranges of all ranges expressly disclosed herein are thus expressly disclosed. These are merely examples of what is specifically intended and all possible combinations of numerical values between the lowest and highest values recited are deemed to be expressly stated in this application in a similar manner.
[0044] Although the present invention is broadly defined above, those skilled in the art will appreciate that the present invention is not limited thereto and that the present invention also includes the exemplary embodiments described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The present invention is described below with reference to the accompanying drawings, in which:
[0046] Figure 1 Displays a double layer composite member.
[0047] Figure 2 Shows three layers of composite members.
[0048] Figure 3 Different geometric shapes of three-layer composite structures are shown, specifically: (a) a hollow composite structure with a square cross-section; (b) a hollow composite structure with a hexagonal cross-section; (c) a solid composite structure with a circular cross-section; and (d) a solid composite structure with a rectangular cross-section.
[0049] Figure 4 Shows the construction of formwork layers and outer layers that can be used to cast a three-layer composite member.
[0050] Figure 5 Shrinkage / expansion of sprayable ductile metallic cementitious compositions (SDMCCs) prepared with OPC and CSA-K cements (where CSA-K contains 7 wt%, 10 wt% and 13 wt% of composite binder, respectively) are shown.
[0051] Figure 6 The shrinkage / expansion of SDMCC prepared with OPC and LC3 / CSA-K cement (where CSA-K contains 10 wt% and 13 wt% of composite binder, respectively) is shown.
[0052] Figure 7 The shrinkage / expansion of SDMCC prepared with CSA-R cement wherein anhydrite comprises 0, 10 wt%, 15 wt% and 20 wt% of CSA-R respectively is shown. DETAILED DESCRIPTION
[0053] The present disclosure relates to multilayer composite structures having advantageous properties, such as the ability to withstand internal and external loads, which can be used in various applications such as pipelines or building components (eg, columns or panels).
[0054] The composite member comprises two or more layers, including an outer layer and an inner layer contacting an inner surface of the outer layer. The inner layer comprises a first cementitious material that expands when cured. Advantageously, the expansion force of the first cementitious material produces a mechanical coupling (frictional bonding) of the inner layer and the outer layer. Another possible advantage of the mechanical coupling is that no adhesive or mechanical anchor (such as a fastener or screw) is required to achieve the coupling of the layers. The coupling and combined properties of the two or more layers can provide a composite member with improved properties such as structural load bearing capacity compared to a single layer of the same cross-sectional size and shape.
[0055] The outer layer may include a second binder material. In certain embodiments, the second binder material shrinks when cured. Advantageously, the second binder material that shrinks when cured can apply a force to the outer surface of the inner layer that produces a compression / coupling effect. Alternatively, the outer layer may include traditional building materials, including but not limited to: metal (e.g., steel), polymers (e.g., PVC), composites (e.g., fiber reinforced plastics), or a combination of two or more thereof. Advantageously, the combination of an inner layer comprising a first binder material and an outer layer comprising a traditional building material can provide improved properties compared to only traditional building materials. For example, compared to only metal (e.g., steel pipes, etc.), for example, in a composite structure comprising a first binder layer and a metal layer, the composite structure can provide corrosion protection. Compared to only PVC (e.g., PVC pipes, etc.), for example, in a composite structure comprising a first binder layer and a PVC layer, the composite structure can also provide increased rigidity.
[0056] The first cementitious material is a cementitious material that expands when cured. The first cementitious material may have a maximum expansion of at least about 1200 με, for example, a maximum expansion of at least about 3000 με, about 3375 με, about 4000 με, or about 4450 με. Those skilled in the art will appreciate that conventional cementitious materials with appropriate expansion properties can be used in composite structures. For example, the first cementitious material may include hydraulic cement and an expansion agent. In certain embodiments, the expansion agent is calcium sulfoaluminate. Preferably, the first cementitious material is a sprayable ductile metallic cementitious composition (SDMCC) as described in WO2021 / 167635A1.
[0057] Those skilled in the art will appreciate that the first and second cementitious materials can be prepared from conventional cementitious materials as long as the desired expansion and contraction properties are obtained. For example, the first and / or second cementitious materials can be fiber reinforced composites such as engineered cementitious composites (ECC). Example formulations of cementitious materials are described in further detail below.
[0058] The exact shape, size, number and materials of the layers may be selected to meet the performance requirements of the application for which the composite structure is intended.
[0059] Composite materials such as Figure 1 As shown, the composite member comprises at least two layers including an inner layer (1) and an outer layer (2). However, the composite member may comprise other combinations of layers depending on the intended application and desired properties of the composite material. For example, the composite member may be as follows Figure 2 The illustrated embodiment comprises at least three layers including an inner layer (10), an outer layer (12) and a coating layer (14), the coating layer (14) comprising a second cementitious material that shrinks when cured.
[0060] In certain embodiments, the composite member may include an additional inner layer. The additional inner layer may be used, for example, as a permanent formwork layer for casting the inner layer. In certain embodiments, the inner layer contacts the outer surface of the formwork layer and the inner surface of the outer layer. The formwork layer may, for example, include a material that can absorb tension from the expanded inner layer. Those skilled in the art may be familiar with formwork and may select appropriate materials for the formwork layer. Suitable materials for the formwork layer include, but are not limited to, metals (e.g., steel), polymers (e.g., PVC), composites (e.g., fiber reinforced plastics), or a combination of two or more thereof.
[0061] The cross-section of the composite member may be circular, rectangular or any other shape. For some applications, the composite member is hollow, e.g. Figure 1 , Figure 2 , Figure 3 as shown in (a) and (b). Figure 3 (a) shows a composite structure having a square cross-section, which comprises an inner layer (30), an outer layer (32) and a coating layer (34), wherein the inner layer (32) comprises a first cementitious material and the coating layer (34) comprises a second cementitious material. Figure 3 (b) shows a composite member having a hexagonal cross-section, comprising an inner layer (40), an outer layer (42) and a coating (44), wherein the inner layer (40) comprises a first binder material and the coating (44) comprises a second binder material. Such applications include pipelines such as civil or industrial pipeline infrastructure for transporting drinking water or wastewater or pipelines for other fluids such as gas or oil. For some applications, the composite member is solid. For example, the composite member can be configured as a solid column or panel that can be used as a building component, such as Figure 3 As shown in (c) and (d). Figure 3 (c) shows a composite structure having a circular cross-section, which comprises an inner layer (50), an outer layer (52) and a coating layer (54), wherein the inner layer (50) comprises a first cementitious material and the coating layer (54) comprises a second cementitious material. Figure 3(d) shows a composite structure having a rectangular cross-section, which includes an inner layer (60), an outer layer (62) and a coating layer (64), wherein the inner layer (60) includes a first cementing material and the coating layer (64) includes a second cementing material. Figure 2 and Figure 3 The composite members shown include an inner layer, an outer layer and a coating layer, but these three-layer composite members can have other combinations of layers. For example, Figure 2 The composite member shown may include a template layer (10), an inner layer (12) and an outer layer (14). Thus, those skilled in the art will appreciate that the shape, size and number of layers and materials of the composite member may be selected depending on the intended application.
[0062] Hydraulic cement
[0063] Hydraulic cement is a material that sets and hardens when mixed with water. Hydraulic cements include, but are not limited to, Portland cement, blended Portland cement, phosphate cement, and belitte cement (dicalcium silicate). Mixtures of any two or more thereof are also contemplated. Preferably, the hydraulic cement is Portland cement.
[0064] Portland cement is a finely ground powder made by grinding clinker composed primarily of hydraulic calcium silicate. Cement may contain up to about 5% gypsum. The amount of gypsum present affects the setting time. The standards for Portland cement are defined in ASTM C150, Standard Specification for Portland Cement, which defines eight types of Portland cement: Type I, Type IA, Type II, Type IIA, Type III, Type IIIA, Type IV, and Type V. Type I cement is a general-purpose ordinary Portland cement (OPC) suitable for all uses where the special properties of the other types are not required. Type III cements are chemically and physically similar to Type I, but they are ground more finely to produce higher early strength.
[0065] The cementitious material's cement component may include hydraulic cement in an amount of about 1 wt % to about 80 wt %, about 20 wt % to about 80 wt %, about 50 wt % to about 80 wt %, or about 60 wt % to about 80 wt % based on the total cement component weight.
[0066] In certain embodiments, the cementitious component comprises reactive aluminosilicates such as calcined clay and / or calcium carbonate such as limestone. Advantageously, replacing a portion of the hydraulic cement with reactive aluminosilicates and / or calcium carbonate can provide a more environmentally friendly composition by reducing the amount of carbon released during the manufacturing process.
[0067] Cementitious materials comprising reactive aluminosilicates and / or calcium carbonate may provide other advantages. For example, limestone calcined clay cement (LC3) pastes have been found to have a finer pore structure than pastes made with OPC. Advantageously, pore refinement provides excellent resistance to chloride attack and good performance in the presence of sulfates, which is particularly evident for the complex environment in pipelines.
[0068] In addition, it was surprisingly found that the cementitious material containing LC3 has a larger strain capacity and a smaller crack width compared to the existing ECC prepared with OPC. The reduced crack width produces a lower permeability. The larger strain capacity can be expected to have a larger deformability. This can produce, for example, a composite member with a higher load and bending capacity.
[0069] The cement component may include reactive aluminosilicate, calcium carbonate, or a mixture thereof in an amount of about 1 wt % to about 80 wt %, about 30 wt % to about 60 wt %, or about 40 wt % to 50 wt % based on the total cement component weight. For example, the cement component may include reactive aluminosilicate in an amount of about 0 to about 50 wt %, about 20 wt % to about 40 wt %, or about 30 wt % based on the total cement component weight. For example, the cement component may include calcium carbonate in an amount of about 0 to about 30 wt %, about 10 wt % to about 20 wt %, or about 15 wt % based on the total cement component weight. In certain embodiments, the ratio of reactive aluminosilicate to calcium carbonate is 2: 1.
[0070] In certain embodiments, the average particle size of the reactive aluminosilicate is about 2 μm to about 40 μm or about 2 μm to about 10 μm. In certain embodiments, the average particle size of the calcium carbonate is about 2 μm to about 100 μm or about 2 μm to about 20 μm.
[0071] In certain embodiments, the cementitious composition comprises about 10 wt % to about 50 wt % OPC, about 20 wt % to about 40 wt % metakaolin, and about 10 wt % to about 20 wt % limestone, based on the total cementitious mixture weight.
[0072] In certain embodiments, a portion of the hydraulic cement can be replaced with mining tailings. For example, the cementitious composition can include mining tailings in an amount of about 1 wt% to about 30 wt% based on the total cementitious composition weight.
[0073] Bulking Agent
[0074] Swelling agents are materials that expand the expansion of cementitious materials during the hydration process. In certain embodiments, the swelling agent can be used to reduce the shrinkage that occurs during the curing of the composition. For example, the swelling agent can be used to reduce the inherent shrinkage properties of the cementitious material to provide a cementitious material suitable as an outer layer (i.e., the second cementitious material). In other embodiments, the swelling agent can be used to provide a cementitious material that expands during curing. Advantageously, expanding the expansion of the cementitious material can reduce the risk of cracking during shrinkage.
[0075] The expansion agent can be used to adjust the expansion properties of the first cementitious material so that when applied to the inner surface of the outer layer and cured, the cementitious material applies an expansion force to the outer layer. The expansion force reduces any space between the cementitious material and the outer layer and increases the mechanical friction between them. Advantageously, the increased mechanical friction can increase the adhesion between the cementitious material and the outer layer. Therefore, compared to a monolithic member, the composite member can have a higher load and bending capacity. In addition, the increased adhesion can reduce the peeling of the cementitious material from the outer layer and the wrinkling and even warping of the composite member. However, those skilled in the art will appreciate that excessive expansion should be avoided in certain embodiments because it can cause deformation of the outer layer. Therefore, the amount of expansion force required depends in part on the material properties of the outer layer.
[0076] Preferred expansion agents include calcium aluminate cement (CAC) and calcium sulfoaluminate cement (CSA). Preferably, the expansion agent is CSA. Based on the weight of CSA, the CaSO 4 ·nH 2 The amount of O is preferably about 1 wt % to 50 wt %, wherein n may be 0, 0.5, 1 or 2.
[0077] The first cementitious material may include an expansive agent in an amount of about 10 wt % to about 60 wt % or about 20 wt % to about 50 wt % based on the total cement component weight. In certain embodiments, the average particle size of the expansive agent is about 2 μm to about 500 μm or about 10 μm to about 30 μm.
[0078] Pozzolans
[0079] Bauxite is a siliceous or siliceous and aluminous material that is generally provided in finely divided form. Bauxite alone has little or no cementitious properties. However, in the presence of water, Bauxite reacts with calcium hydroxide released by hydration of hydraulic cement to form calcium silicate hydrate or other cementitious compounds. Advantageously, Bauxite can increase the binder fracture toughness of the cementitious material, thereby producing a higher ductility of the cured cementitious material. Bauxite can also be used to modulate the rheology of the cementitious material. Advantageously, the rheology of the cementitious material can be modulated to increase the pumpability and / or sprayability of the composition.
[0080] Generally, any siliceous or siliceous and aluminous material that reacts with calcium hydroxide in the presence of water is suitable for use in the binder. Examples of suitable pulverized gases include, but are not limited to, fly ash, steel slag, granulated blast furnace slag, diatomaceous earth, silica fume, calcined clays such as metamorphosed kaolin, calcined shale, volcanic ash, pumice, burnt silica-rich organic matter such as rice husk ash, and mixtures of any two or more thereof. Preferably, the pulverized gas component comprises fly ash such as defined in ASTM C618. In certain embodiments, the fly ash is Type C fly ash and / or Type F fly ash.
[0081] In certain embodiments, the cementitious component comprises silica fume. Advantageously, silica fume can increase the compressive strength of the cementitious material and / or improve fiber / matrix interface bonding in those embodiments where the first cementitious material comprises fibers.
[0082] The composite binder may include a pulverized cement component in an amount of about 0 to about 3 times the weight of the cement component. Preferably, the composite binder includes a pulverized cement component in an amount of about 1 to about 3 times, preferably about 2 to about 3 times, and more preferably about 2 to about 2.5 times the weight of the cement component.
[0083] fiber
[0084] Fiber is used to strengthen and cure cementitious materials. Suitable fiber can be selected according to various characteristics including the expected cost of fiber, mechanical properties, physical properties and bonding properties. The properties of cementitious materials can be affected by factors such as the length, diameter, chemical composition, rigidity, density and strength of the fiber. Fiber can be selected to transmit the load through the crack when the composite is loaded to exceed the elastic stage. Their load-bearing behavior can be adjusted to balance fiber breakage and fiber sliding, i.e. controlled fiber bridging behavior. When applying load on the composite, too much fiber breakage and fiber sliding are undesirable, so this will limit the composite ductility or cause excessive crack width and damage the composite ductility. Advantageously, fiber can improve the strain hardening and tensile ductility of composite members and limit crack width.
[0085] Fibers suitable for use in the cementitious material include, but are not limited to, polymeric fibers, inorganic fibers (e.g., basalt fibers and glass fibers), metal fibers (e.g., steel fibers), carbon fibers, plant-based fibers (e.g., cellulose fibers and lignocellulose fibers), and mixtures of any two or more thereof. Preferably, the fibers are polymeric fibers, i.e., fibers composed of polymeric materials such as polyolefins (e.g., polyethylene or polypropylene), polyacrylic acid, polyester, polyvinyl alcohol, polyamides (e.g., nylon), or any two or more thereof. More preferably, the fibers are polypropylene fibers and more preferably high tenacity polypropylene fibers. In certain embodiments, the fibers are short discontinuous fibers.
[0086] The upper limit of fiber concentration is dominated by pumpability and sprayability, while the lower limit is dominated by the ability to provide strain hardening (ductility) behavior opposite to brittle or semi-brittle behavior. For example, the fiber can have an amount of about 0.1 v / v% to less than 4 v / v%, about 1 v / v% to about 3 v / v%, or about 1.5 v / v% to about 2.3 v / v% based on the total composition volume (i.e., the volume of the composition including water). In certain embodiments, the fiber length is about 4 mm to about 25 mm, about 6 mm to about 20 mm, or about 8 mm to about 12 mm. In certain embodiments, the fiber diameter is about 10 μm to about 150 μm or about 10 μm to about 60 μm.
[0087] Superplasticizer
[0088] In certain embodiments, the cementitious material further comprises a superplasticizer, also known as a high-efficiency water reducer. Superplasticizers can be added to cementitious materials to affect the rheology of the composition. Advantageously, superplasticizers can reduce the amount of water required to maintain the pumpability and sprayability of the cementitious material.
[0089] Therefore, superplasticizers are generally added to the cementitious material in an amount effective to obtain a composition having the desired pumpability and sprayability. Those skilled in the art will appreciate that the amount of superplasticizer required to obtain the desired pumpability and sprayability may depend on other components of the composition, such as the water content of the composition. For example, superplasticizers may be included in the cementitious material in an amount of about 0.1 wt % to 10 wt %, about 0.3 wt % to 3 wt %, or about 0.5 wt % to 1.5 wt %, based on the total composition weight.
[0090] Generally, any superplasticizer known in the art is suitable for use in the cementitious material. Superplasticizers include, but are not limited to, sulfonated melamine (e.g., sulfonated melamine formaldehyde condensate), sulfonated naphthalene (e.g., sulfonated naphthalene formaldehyde condensate), polycarboxylic acid ethers (e.g., 190), modified wood sulfonates and mixtures of any two or more thereof.
[0091] Granules
[0092] The cementitious material may further comprise aggregates such as sand, ground stone and lightweight aggregates. The addition of lightweight aggregates may reduce the density of the cementitious material. The addition of lightweight aggregates may also allow for increased thickness to be sprayed, particularly on horizontal upper surfaces. If the amount of lightweight aggregate is large, the particle size becomes important, otherwise strain hardening cannot be achieved. Typically, the average particle size is from about 10 μm to about 1000 μm, from about 10 μm to about 200 μm, or from about 30 μm to about 100 μm.
[0093] Lightweight particulates may include, but are not limited to, ground rubber (eg, from scrap tires), hollow glass spheres, cenospheres, expanded mica, and microspheres (eg, glass, ceramic, or polymer microspheres).
[0094] In addition to or in place of the lightweight aggregate, the binder material may further include gas bubbles. The gas may be added during processing of the binder material by physical means such as bubbling or aeration. Alternatively, the gas may be added chemically, such as hydrogen produced by the reaction of aluminum powder with an alkaline composition or the reaction of Si-H functionalized silane with water. In certain embodiments, a stabilizing substance is added to help prevent the coalescence of adjacent gas bubbles. In certain embodiments, the volume percentage is limited to provide a pressure equal to or greater than about 1400 kg / m 3 , preferably equal to or higher than about 1500 kg / m 3 If significant agglomeration into large voids occurs, the strength properties of the composite, especially the strain hardening behavior, will be compromised. Air bubbles can be used in conjunction with other lightweight aggregates. Advantageously, the volume fraction of air bubbles in such formulations can be kept small so that agglomeration can be minimized. For example, in a 1300 kg / m 3 In a composite having a target density of about 1600 kg / m 3 density and add other lightweight fillers to reduce the density to the target range.
[0095] Other additives
[0096] The cementitious material may further comprise other additives as known in the art, such as viscosity agents and / or retarders.
[0097] For example, the viscosity agent can be a cellulose derivative, such as hydroxypropylmethylcellulose (HPMC). The viscosity agent can be included in the binder material in an amount of about 0 to about 1 wt%, about 0.03 wt% to about 0.5 wt%, or about 0.05 wt% to about 0.2 wt%, based on the total binder weight (i.e., the weight of the composition without water). The viscosity agent increases the ability of the composite to accumulate thickness on the substrate and also helps to evenly disperse the fibers in the matrix.
[0098] The cementitious material may include a retarder. Conventional retarders may be used. A preferred retarder is citric acid which may be advantageously used in conjunction with CSA. The retarder may be included in an amount of about 0.01 wt % to about 10 wt %, about 0.1 wt % to about 2 wt %, or about 0.2 wt % to about 1.5 wt % based on the total binder weight. The retarder may increase the working time of the cementitious material during the spraying process. However, those skilled in the art will appreciate that too much retarder may reduce the strength and ductility of the cementitious material.
[0099] water
[0100] The amount of water in the cementitious material affects various properties of the composition. In certain embodiments, the water content should be sufficient to obtain a pumpable and sprayable composition. Generally, higher water contents reduce viscosity and increase sprayability, while lower water contents increase cohesion and allow thicker coatings. The amount of water required to provide a pumpable and sprayable composition can be easily determined by routine experimentation and can be reduced by including a superplasticizer as described above.
[0101] In certain embodiments, the water to binder ratio is about 0.2 to about 0.5. Preferably, the water to binder ratio is about 0.2 to about 0.4, more preferably about 0.3.
[0102] Preparation of cementitious materials
[0103] The cementitious materials of the present invention may be prepared by conventional techniques. The components may be mixed separately with water or certain components may be premixed. In certain embodiments, water is added to a premix of dry binder components to obtain a wet mixture and fibers are added to the wet mixture. In certain embodiments, a superplasticizer is mixed with water to form a solution, the solution is added to a premix of dry binder components to obtain a wet mixture and fibers are added to the wet mixture. In certain other embodiments, the dry components may be provided in a "ready-mix" composition, such as a premix of dry binder components and fibers that is mixed with water prior to use to form the cementitious material.
[0104] Preparation of composite materials
[0105] The composite structure can be prepared by spraying a first binder material onto the inner surface of the outer layer. The first binder material is cured to form the inner layer and provide the composite structure. Advantageously, when the first binder material is SDMCC, the curing process is exothermic and no heat input is required to initiate the hydration and chemical reactions for curing. In this process, the outer layer acts as a permanent template. When the composite material includes a coating, a second binder material is sprayed onto the outer surface of the outer layer and cured to form the coating. The first and second binders can be sprayed onto the inner and outer surfaces of the outer layer simultaneously or sequentially in any order.
[0106] Alternatively, the composite member may be prepared by a casting process. Figure 4 As shown, the outer layer (74) and the formwork layer (76) may have a cavity (78) between the two layers. A first cementitious material may be cast in the cavity (78) and cured to provide a composite structure. In some embodiments, the process may further include spraying a second cementitious material on the outer layer and curing the cementitious material.
[0107] The following non-limiting examples are provided to illustrate the present invention and in no way limit its scope.
[0108] Example
[0109] 1. Material composition and processing
[0110] Example mixtures are listed in Table 1. Cement was Type I Portland cement (PC1) from Lafarge Cement Company, Michigan, USA. Two expansive cements from CTS Cement Manufacturing Company and from Royal White Cement Company were used and were defined as CSA-K and CSA-R, respectively. Metamorphosed kaolin (MK) was from Sika Company, New Jersey, USA. The anhydrite was Terry-Alba No. 1 from USG. The limestone (LS) was from Omya Canada The fly ash (FA) was Class C fly ash from Boral Material Technologies with a size distribution of 10 μm to 100 μm. The superplasticizer (SP) was from GCP Applied Technologies. Hydroxypropylmethylcellulose (HPMC) as viscosity agent was from Fisher Scientific. Polypropylene (PP) fibers were present in an amount of 2% by volume and had a diameter of 12 μm, a length of 10 mm, a Young's modulus of 6 GPa and a tensile strength of 850 MPa and were from Brasilit, Saint-Gobain, Brazil.
[0111] Table 1
[0112]
[0113] The names in Table 1 express the composition of the binder. OPC and LC3 represent binders prepared by general Portland cement and limestone calcined clay cement, respectively. K07, K10 and K13 represent CSA-K to binder ratios of 7 wt%, 10 wt% and 13 wt%. R13-C0, R13-10, R13-15 and R13-20 represent CSA-R and anhydrite to binder ratios of 13 wt%, wherein the anhydrite ratio is 0, 10 wt%, 15 wt% and 20 wt% of the total weight of CSA-R and anhydrite. The wt% ratios of PC1, MK and LS in LC3 cement are 55%, 30% and 15%.
[0114] SDMCC was prepared by mixing all dry ingredients (PC1, CSA, anhydrite, MK, LS, FA and HPMC) in a tumble mixer for 10 minutes. Water was gradually added along with SP and mixed for 6 minutes. Finally, PP fibers were added followed by mixing for 6 minutes.
[0115] 2. Expansion characteristics
[0116] The samples for shrinkage / expansion measurement were cast in corner column molds (25×25×300 mm). The shrinkage / expansion measurement was performed as early as possible after demoulding without destroying the sample and marked as the "zero time" of deformation. For the mixtures in Table 1, the demoulding time was 20 hours for OPC; 10 hours for K07; 5 hours for K10, K13 and LC3-K13; 8 hours for LC3-K10; 3 hours for R13-C0, R13-C10, R13-C15 and R13-C20. The samples were stored in an environment of 20±2°C and 40±5% relative humidity (RH). The length change of the samples was tested according to ASTM C490 / C490M-17.
[0117] 2.1 Drying shrinkage / expansion
[0118] The shrinkage / swelling versus aging curves of the compositions in Table 1 are shown in Figures 5 to 7 , where the negative sign (on the y-axis) indicates shrinkage and the positive sign indicates expansion. Table 2 lists the characteristic values of shrinkage / expansion at 28 days. For the SDMCC prepared from OPC, the shrinkage increases continuously to -1434με at 28 days. Such a large shrinkage can lead to rupture under restraint conditions, thereby reducing the ductility of the material. The SDMCC using CSA-K shows the characteristics of initial expansion followed by shrinkage. The maximum expansion occurs at about 2 days of aging. For compositions K07, K10 and K13, the maximum expansion values are 779με, 2418με and 3756με as the CSA-K ratio changes. However, in the case of 7wt% CSA-K cement in the composite binder, the SDMCC still shows a -823με shrinkage at 28 days. The expansion of K10 and K13 at 28 days was 1139με and 2026με, respectively. The expansion of ECC using LC3 is slightly less than that of OPC. For LC3-K10 and LC3-K13, the expansions were 838 με and 1722 με.
[0119] The type of CSA cement also affects the expansion value. CSA-R has less CaSO than CSA-K. 4 Even when the content of CSA-R was 13 wt % of the composite binder (R13-C0), the shrinkage of R13-C0 was -834 με at 28 days and showed no expansion. Increasing the substitution of CSA-R with anhydrite reduced the shrinkage and R13-C20 had an expansion of 489 με at 28 days. Without wishing to be bound by theory, it is believed that the CaSO 4 The amount of gypsum (or anhydrite) affects the production of ettringite, which is the main expansion hydration product of CSA cement.
[0120] 2.2 Minimum Expansion
[0121] Assuming linear material behavior, the pressure due to expansion can be expressed as:
[0122] p = E 1 ε 1 -E 2 ε 2 (1)
[0123] where p is the pressure exerted by the expanding SDMCC; ε 1 is the maximum expansion of SDMCC; ε 2 is the difference between the maximum expansion and the residual strain at 28 days; E 1 is the effective modulus between time zero and the maximum dilation time and; E 2 is the effective modulus between the maximum expansion time and 28 days. ε 1 and ε 2 It can be tested by the drying shrinkage / expansion test according to ASTM C490 / C490M-17, and the values are listed in Table 2. 1 and E 2 It is the effective modulus affected by stress release and time development. During early aging (before 3 days), creep is more pronounced than during later aging (3 to 28 days). In addition, even for fast-hardening SDMCC materials, the elastic modulus is smaller during early aging.
[0124] Assumption E 1 =kE 2 , pressure can also be expressed as:
[0125] f = (kε 1 - ε 2 )E 2 (2)
[0126] where k is defined as the coefficient of the effective modulus. k is determined by the combined effect of the material elastic modulus development and the boundary constraints. Advantageously, to ensure that the SDMCC has a coupling effect on the outer layer or template layer, f should be greater than 0. In other words, kε 1 –ε 2 Should be greater than 0. According to Zhu H. et al. Double feedback control method for determining early-age restrained creep of concrete using a temperature stress testing machine. Materials, 2018, 11(7), 1079, it seems reasonable to assume k = 0.5.
[0127] Table 2
[0128]
[0129] For the mixtures in Table 2, the maximum expansion and expansion after 28 days for OPC are different from those for K07, K10 and K13; however, for OPC, K07, K10 and K13, the difference between the maximum expansion and the expansion after 28 days (i.e., ε 2 ). It is experimentally found that for OPC-based SDMCC, ε 2 is about 1531 με and 605 με for LC3-based SDMCC. Therefore, for OPC-based SDMCC, the maximum expansion ε 1 =ε 2 / k is preferably at least 3062 με (1531 / 0.5) to provide the desired coupling effect. For LC3-based SDMCC, the maximum expansion is preferably at least 1210 με (605 / 0.5).
[0130] 3. Preparation of prefabricated uniform cross-section components made of multi-layer cementitious compositions
[0131] Multilayer cementitious composition prefabricated iso-section members can be prepared by selecting the appropriate compositions exemplified in Table 1. For example, R13-C15 achieves a long-term shrinkage of 326 με and is therefore suitable for use as an outer layer. Although OPC also shrinks, a long-term shrinkage of 1434 με will lead to cracking, which is undesirable. For the inner layer, a material with controlled expansion is required. LC3-K13 provides a long-term expansion of 1722 με and can be used as such an inner layer.
[0132] References to patent specifications, other external documents or other information sources in this specification are generally for the purpose of providing a context for describing the features of the invention. Unless specifically stated otherwise, reference to external documents should not be construed as an admission that these documents or information sources are prior art or form part of the common general knowledge in the art in any jurisdiction.
[0133] It is not intended to limit the scope of the invention to the examples described above. It will be appreciated by those skilled in the art that many variations are possible without departing from the scope of the invention as set forth in the appended claims.
Claims
1. Composite materials, including: - an inner layer comprising a first cementitious material, and - Outer layer, The inner layer substantially covers an inner surface of the outer layer and the first bonding material is an intumescent material that applies a force to the inner surface of the outer layer.
2. A method for manufacturing a composite member according to claim 1, the method comprising: - spraying an uncured mixture of the first cementitious material onto the inner surface of the outer layer; as well as - Curing said first cementitious material to obtain said composite structure.
3. A method of manufacturing a composite structure comprising an inner layer, a formwork layer and an outer layer, the inner layer comprising a first cementitious material that expands when cured, wherein the inner layer contacts an outer surface of the formwork layer and an inner surface of the outer layer, wherein the method comprises: - providing said template layer and said outer layer with a cavity between the two layers; - casting an uncured mixture of the first cementitious material in the cavity between the formwork layer and the outer layer; as well as - Curing said first cementitious material to provide said composite member.
4. A composite member as claimed in claim 1 or a method as claimed in claim 2 or 3, wherein the first cementitious material comprises an expansion agent.
5. A composite member as claimed in claim 1 or 4 or a method as claimed in any one of claims 2, 3 or 4, wherein the first cementitious material has a maximum expansion of at least about 1200 με.
6. A composite member as claimed in any one of claims 1, 4 or 5 or a method as claimed in any one of claims 2 to 5, wherein the outer layer comprises a second cementitious material.
7. A composite member or method as claimed in claim 6, wherein the second cementitious material shrinks when cured.
8. A composite member or method as claimed in claim 6 or 7, wherein the second cementitious material has a shrinkage of less than about 500 μm when cured.
9. A composite member or method as claimed in claim 6 or 7, wherein the second cementitious material has a shrinkage of less than about 1000 με when cured.
10. A composite member or method as claimed in any one of claims 6 to 9, wherein the first cementitious material and / or the second cementitious material comprises a composite binder.
11. A composite structure or method as claimed in claim 10, wherein the composite binder comprises a cement component and a plastic component.
12. A composite member or method as claimed in any one of claims 6 to 11, wherein the first cementitious material and / or the second cementitious material comprises fibres.
13. A composite member or method as claimed in any one of claims 6 to 12, wherein the first cementitious material and / or the second cementitious material is sprayable.
14. The composite member of any one of claims 1, 4 or 5 or the method of any one of claims 2 to 5, wherein the outer layer comprises a metal, a polymer, a composite or a combination of any two or more thereof.
15. The method of claim 3, wherein the template layer comprises a metal, a polymer, a composite, or a combination of any two or more thereof.
16. A composite member as claimed in any one of claims 1 or 4 to 15 or a method as claimed in any one of claims 2 to 15, wherein the composite member is prefabricated.
17. A composite member as claimed in any one of claims 1 or 4 to 16 or a method as claimed in any one of claims 2 to 16, wherein the composite member is hollow or solid.
18. A composite member as claimed in any one of claims 1 or 4 to 17 or a method as claimed in any one of claims 2 to 17, wherein the composite member is in the form of a tube, column or plate.
19. A composite member prepared according to the method of any one of claims 2 to 18.
20. Use of a composite member as claimed in any one of claims 1 or 4 to 19 as a tube, wherein the composite member is hollow.
21. The use according to claim 20, wherein the cross section of the composite member is circular.
22. The use according to claim 20 or 21, wherein the pipe is used to transport water, gas or oil.
23. Use of a composite member as claimed in any one of claims 1 or 4 to 19 as a building element.
24. The use according to claim 23, wherein the building element is a column or a panel.
Citation Information
Patent Citations
Sprayable cementitious composition
WO2021167635A1